An explicit modal discontinuous Galerkin method for Boltzmann transport equation under electronic nonequilibrium conditions - Singh, Satyvir (2022)
The present paper deals with the development of a numerical scheme for the solution of two-dimensional Boltzmann transport equation (BTE) under electronic nonequilibrium conditions. A two-dimensional explicit modal discontinuous Galerkin (DG) method with uniform meshes is developed for solving the BTE in conjunction with the relaxation time approximation. The spatial discretization is carried out using a high-order DG method, where the polynomial solutions are represented using scaled Legendre basis functions. A third-order explicit SSP-RK scheme is applied for temporal discretization to the resulting semi-discrete ordinary differential equation. The analytic steady state solution of BTE at low electromagnetic field is considered as the validation study. The numerical scheme is applied to the description of electron transport in non-linear dynamic conductivity based on static electric field. The electrical and Hall conductivities with nonequilibrium conditions is estimated for the BTE solution in presence of the electromagnetic field. These transport coefficients are also examined with the dependence of temperature and chemical potential. It is observed that the electrical and Hall conductivity decreases in the presence of a magnetic field. Numerical results demonstrate the potential advantages of the high-order scheme in treating ultrafast nonequilibrium dynamics.